On convolutions on configuration spaces. II. spaces of locally finite configurations - Finkelshtein, D. L. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider the convolution of probability measures on spaces of locally finite configurations (subsets of a phase space) as well as their connection with the convolution of the corresponding correlation measures and functionals. In particular,the convolution of Gibbs measures is studied. We also describe a relationship between invariant measures with respect to some operator and properties of the corresponding image of this operator on correlation functions.